Unter Wilden am Amazonas - Domville-Fife, Charles W. (Charles William), 1886-1960; Langenberg, Hanns, 1892-1956 (Salt Lake City, UT : Project Gutenberg, 2024)
"Unter Wilden am Amazonas" by Charles W. Domville-Fife is an adventurous account written in the early 20th century. This work recounts the author's explorations and experiences among native tribes of the Amazon, including headhunters and cannibals. The book likely delves into the rich tapestry of the Amazon rainforest, its indigenous peoples, and the challenges and marvels encountered in such a wild and largely uncharted region. The opening of the book sets the stage for Domville-Fife$1 (Bs expedition by detailing the historical context of the Amazon's discovery by Europeans and the romanticized myths that emerged about its land and peoples. It introduces the various risks and perils faced by explorers, including hostile tribes, the harshness of the environment, and the allure of hidden treasures. The narrative quickly transitions into Domville-Fife's personal journey, emphasizing his preparations and motivation to venture into the depths of the Amazon, highlighting the stark contrast between the civilization he departs from and the untamed wilderness he seeks to explore. (This is an automatically generated summary.)s
Release date is 2024-11-04
The Online Distributed Proofreading Team at https://www.pgdp.net
Keywords: Amazon River Valley; Amazon River; Indians of South America -- Amazon River Valley